EEG Characteristics and Diagnostic Implications in Childhood Headache: A Multi-Center Study - Rho, Young Il; Kim, So Hyun; Kang, Hoon-Chul; Lee, Yun-Jin; Kim, Young Ok; Kim, Sung Koo (Frontiers in Neurology, 2020)
Introduction: Epilepsy and migraines are frequently observed as comorbidities, with the occurrence of one disorder increasing the probability of the other. The aim of our study was to evaluate the EEG characteristics depending on the type of headache, and the implication of EEGs in headache patients, comparing the clinical characteristics and treatments between the headache patients with normal and abnormal EEGs. Methods: We conducted a retrospective analysis by reviewing the medical records of 259 patients with headaches who visited the department of pediatrics in five university hospitals and underwent EEGs over a period of three years. Based on the data entered, analyses of the following items were conducted: 1) comparison of the EEG abnormalities depending on the type of headache and the characteristics of the EEG findings, 2) comparison of the clinical characteristics between patients with normal and abnormal EEGs Results: Of the 259 patients, 31 showed abnormal EEGs, while 228 had normal EEGs. Of the 31 patients with abnormal EEGs, 17 showed epileptiform discharges, and 11 showed rhythmic slowing. The frequency of EEG abnormalities was significantly high in patients with migraines with auras than other types of headache. The Pediatric Migraine Disability Assessment (PedMIDAS) score was significantly higher in the abnormal EEG group compared to the normal EEG group (p = 0.001). Conclusion: The results of this study suggest that the abnormal EEG group had more significant disruptions in their daily lives due to headaches than the normal EEG group and patients with migraines with aura may need EEGs and they might also have overlapping pathophysiologic mechanisms with epilepsy